Evaluation of the Implementation of Regional Public Service Agency in Sultan Imanuddin Pangkalan Bun Hospital - Gusti Muhamad Syariyansyah; Ellina, Agusta Dian; Sentot Imam Suprapto (Universitas STRADA Indonesia, 2025)
Background: Currently, public service agencies, both private and government-owned, are demanding excellent service. Quality customer service is the key to success and the basis for building customer success and trust. Purpose: This research was conducted to explore the evaluation of the implementation of the Regional Public Service Agency at Sultan Imanuddin Pangkalan Bun Hospital. Methods: The design of this research is qualitative research with a phenomenological approach with the focus of the research directed at exploring the evaluation of the implementation of the Regional Public Service Agency at Sultan Imanuddin Pangkalan Bun Hospital. Apart from that, with a qualitative approach. The informants in this research were the owners or people in charge of the clinic, a total of 5 (Five) people with triangulation of sources. Results: The implementation of the Regional Public Service Agency (BLUD) at Sultan Imanuddin Hospital Pangkalan Bun provides benefits in financial management, human resources and decision making. Even though it requires socialization, technology, training and commitment from all parties, the implementation of BLUD still increases efficiency in managing health services. Obstacles that arise, such as ineffective management, policy changes, and lack of resources, are still overcome by increasing transparency and efficiency. Conclusion: The implementation of BLUD at Sultan Imanuddin Pangkalan Bun Hospital is beneficial in financial management and health services, although there are obstacles such as less effective management.